A Study on Vehicle Differential system (International Journal of Scientific Research and Management (IJSRM), 2017)
In light commercial vehicles and other wheeled vehicle, an open differential is a device that allows each driven driven wheel to rotate in different speeds during a curve or in limited grip conditions. When one of the wheels loses the grip the differential will direct all the torque available to the wheel that is spinning making the vehicle get stuck. The automobile industry is always looking for opportunities in terms of weight and size reduction. This new concept is more compact, lighter, quieter, more efficient and with higher performance. In automobile and other wheeled vehicles, the differential allows the outer drive wheel to rotate faster then the inner drive wheel during a turn. During ordinary conditions, when the vehicle is driven down straight road, or if the difference between speeds of the two(rear) wheels is below a specified limit, no signal will be generated by the electronic circuit. This helps the vehicle negotiate the turns with better traction control as differential action is unaltered. But if the difference between speeds is beyond a specified limit, the signal will be generated by the electronic circuit which will actuate the pneumatic circuit.